Investigating The Effect of Transcutaneous Electrical Nerve Stimulation on The Severity of Restless Legs Syndrome in Hemodialysis Patients - Abolfazl Kalmishi; Ali Abedi; Katayoun Samadi; HamidReza Shoraka; Mostafa Rad (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Restless leg syndrome (RLS) is one of the most common complications of hemodialysis patients. Transcutaneous electrical nerve stimulation (TENS) may affect RLS by reducing pain and increasing blood supply and oxygen supply. The present study was conducted to determine the effect of electrical nerve stimulation through the skin on the severity of restless leg syndrome in hemodialysis patients. Materials and Methods: This clinical trial study was conducted on 60 patients undergoing hemodialysis treatment in the dialysis department of Vasei Sabzevar and Imam Khomeini Esfrain Hospitals, from December of 2022 to March 2023. The participants were randomly selected in two intervention (30 people) and control groups (30 people). TENS was used with a frequency of 100 Hz in the intervention group and 20 Hz in the control group. The severity of RLS was measured before and after intervention using the RLS questionnaire in two groups. Data analysis was done using SPSS 22 and statistical tests (independent t, paired t-test, and chi-square). Results: After the intervention, the severity of RLS in the intervention and control groups was 13.93±2.56 and 17.63±3.30, respectively, and the independent t-test showed a significant difference (p=0.001). Conclusion: The results of this study showed that the use of TENS is effective in relieving of RLS in hemodialysis patients, so it can be used as a complementary method in the treatment of hemodialysis patients.